Strategy-Pedagogy Mismatch in Teaching Grammar to Gen Z EFL Learners in West Sulawesi - Nihla Afdaliah; Sri Ananda Pertiwi; Wahyu; Muhammad Mukhtar Aliyu (Eduvelop: Journal of English Education and Development, 2026)
Despite continuous pedagogical refinement and extensive use of multimedia resources, grammar learning outcomes among EFL learners often remain below academic expectations, particularly in higher education contexts where grammatical accuracy is essential for academic writing. This study aims to investigate the mismatch between grammar teaching strategies and grammar learning strategies among Gen Z EFL learners, and to examine how such mismatch influences grammar learning effectiveness. Employing an explanatory mixed-method design, quantitative data were collected through a grammar learning strategy questionnaire administered to undergraduate students and a grammar teaching strategy inventory completed by the lecturer, while qualitative data were obtained from semi-structured interviews and analysis of grammar-related writing tasks. The findings indicate that learners employ a range of grammar learning strategies, with a strong reliance on technology-mediated strategies. Grammar instruction is characterized by explicit explanation and intensive multimedia use; however, opportunities for interactive practice and application-oriented assessment remain limited. This condition generates strategy–pedagogy mismatch, manifested in instruction–practice mismatch, assessment–application mismatch, and strategy–cognition mismatch. Qualitative evidence shows that although learners perceive grammar instruction as clear and supportive, many struggle to retain grammatical knowledge and apply it independently in writing tasks. These conditions contribute to fragile grammar retention, limited grammar internalization, and cognitive passivity in grammar learning. The study concludes that persistent grammar learning difficulties are not caused by insufficient instructional effort, but by strategy–pedagogy mismatch. Pedagogically, the findings suggest the need for grammar instruction that integrates practice-intensive learning cycles, application-oriented assessment, and pedagogically guided use of digital tools to strengthen grammar retention and promote independent grammatical control among Gen Z EFL learners.